What a sparrow bib can reveal - Erritzoe, Johannes (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
It has long been known that male House Sparrows ("Passer domesticus") with a large bib dominate other sparrows with smaller bibs. Also during the breeding season females prefer males with large badges, as the bib is also called, even though these males show more sexual interest in other females than males with smaller bibs (Moller 1987). But why do females prefer an unfaithful partner? Is it because of his large bib, or is the answer more complex?
Keywords: bib; bursa of Fabricii; fault bars; feather lice; House Sparrows; Passer domesticus